In-Focus Electrostatic Zach Phase Plate Imaging for Transmission Electron Microscopy with Tunable Phase Contrast of Frozen Hydrated Biological Samples. (2nd January 2014) - Frindt, Nicole; Oster, Marco; Hettler, Simon; Gamm, Björn; Dieterle, Levin; Kowalsky, Wolfgang; Gerthsen, Dagmar; Schröder, Rasmus R.
Abstract Transmission electron microscopy (TEM) images of beam sensitive weak-phase objects such as biological cryo samples usually show a very low signal-to-noise ratio. These samples have almost no amplitude contrast and instead structural information is mainly encoded in the phase contrast. To increase the sample contrast in the image, especially for low spatial frequencies, the use of phase plates for close to focus phase contrast enhancement in TEM has long been discussed. Electrostatic phase plates are favorable in particular, as their tunable potential will allow an optimal phase shift adjustment and higher resolution than film phase plates as they avoid additional scattering events in matter. Here we show the first realization of close to focus phase contrast images of actin filament cryo samples acquired using an electrostatic Zach phase plate. Both positive and negative phase contrast is shown, which is obtained by applying appropriate potentials to the phase plate. The dependence of phase contrast improvement on sample orientation with respect to the phase plate is demonstrated and single-sideband artifacts are discussed. Additionally, possibilities to reduce contamination and charging effects of the phase plate are shown.